Acute focal bacterial nephritis. Issue 5 (May 1985) - Lawson, G R; White, F E; Alexander, F W
Abstract : In the kidney, acute focal parenchymal infection without liquefaction can produce a 'mass lesion' that may mimic an abscess or tumour, both clinically and radiologically. Ultrasound and computed tomography can differentiate between these lesions and allow appropriate antibiotic treatment to be used safely, avoiding unnecessary surgical intervention.